POTENTIAL OF MAIZE, MILLET AND RATTLEBOX TO BREAK THE CYCLE OF ð˜šð˜±ð˜°ð˜¥ð˜°ð˜±ð˜µð˜¦ð˜³ð˜¢ ð˜¦ð˜³ð˜ªð˜¥ð˜¢ð˜¯ð˜ªð˜¢ (CRAMER) (LEPIDOPTERA: NOCTUIDAE) - Favetti, Bruna Magda; Massarolli, AngÃ©lica; Butnariu, Alessandra Regina; Foerster, LuÃs Amilton (REVISTA DE AGRICULTURA, 2021)
This study evaluated the effect of different crops grown during soybean offseason on the development and reproduction of Spodoptera eridania (Cramer). The experiment was conducted in laboratory at 25°C±1°C, relative air humidity of 70%±10% and a 12h photophase. The plants evaluated were cotton (FMT 701), sunflower (Embrapa 122-V2000), rattlebox (Crotalaria spectabilis Roth), corn (Dekalb 370) and millet (DR-300). The less suitable hosts for the survival of S. eridania were rattlebox, corn and millet. Only cotton and sunflower the specie completed its development (egg to adult). Corn, millet and rattlebox were the crops that most affected the performance of S. eridania, and therefore they could potentially be used in the soybean offseason period to interrupt the life cycle of this species, and thus reduce population incidence during soybean season.